Animal Models of Diabetic Macrovascular Complications: Key Players in the Development of New Therapeutic Approaches - Suvi E. Heinonen; Guillem Genové; Eva Bengtsson; Thomas Hübschle; Lina Åkesson; Katrin Hiss; Agnes Benardeau; Seppo Ylä-Herttuala; Ann-Cathrine Jönsson-Rylander; Maria F. Gomez (Journal of Diabetes Research)
Diabetes mellitus is a lifelong, incapacitating metabolic disease associated with chronic macrovascular complications (coronary heart disease, stroke, and peripheral vascular disease) and microvascular disorders leading to damage of the kidneys (nephropathy) and eyes (retinopathy). Based on the current trends, the rising prevalence of diabetes worldwide will lead to increased cardiovascular morbidity and mortality. Therefore, novel means to prevent and treat these complications are needed. Under the auspices of the IMI (Innovative Medicines Initiative), the SUMMIT (SUrrogate markers for Micro- and Macrovascular hard end points for Innovative diabetes Tools) consortium is working on the development of novel animal models that better replicate vascular complications of diabetes and on the characterization of the available models. In the past years, with the high level of genomic information available and more advanced molecular tools, a very large number of models has been created. Selecting the right model for a specific study is not a trivial task and will have an impact on the study results and their interpretation. This review gathers information on the available experimental animal models of diabetic macrovascular complications and evaluates their pros and cons for research purposes as well as for drug development.